Recognition and reinforcement of arbitral award [electronic resource] - Ten, Yuen Her, 1991-, author 605538; Maizon Hashim, supervisor 577586; Fakulti Alam Bina 8041 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2016